Evaluasi Efektivitas Sistem Informasi Dalam Strategi Pemasaran Pariwisata Masjid Istiqlal Di Instagram - Nurul Putri Puspitasari; Diaz Bagoes Dermawan (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
The Government's strategy in marketing destinations is an important part of tourism development, especially together with the Istiqlal Mosque Management to promote religious tourism destinations so that they are known to more audiences using Instagram. This research aims to find out how tourism marketing communication strategies are used to promote the Istiqlal Mosque as a religious tourism destination through Instagram social media. Along with the development of increasingly sophisticated technology, especially nowadays, generation 4.0 has entered the sophistication of digital technology that can be held in the hand. Instagram is a program that originates from the creation of New Media, which uses the internet with the aim of being able to communicate long distances and unlimitedly and its network spreads unlimitedly as long as the internet is still running. Researchers use the theory of The Circular Model of SoMe For Social Communication, this theory can make it easier for practitioners on social media, Instagram. The paradigm of this research is post-positivism. This research uses a qualitative approach with qualitative descriptive methods. The results of this research show that the DKI Jakarta Tourism Department together with the Istiqlal Mosque have demonstrated strategic results in promoting the Istiqlal Mosque, via Instagram. This strategy includes presenting history, interesting visual content, and containing the most up-to-date information on social media. This research identified several challenges, the lack of information to the public about religious tourism, perhaps in the future the DKI Jakarta Provincial Tourism and Creative Economy Department together with the Istiqlal Mosque Management will further promote many tourism activities, such as continuing the Istiqlal Fair. To achieve success in the marketing promotion of the Istiqlal Mosque destination in providing information to tourists to become more familiar with religious tourism destinations through social media or directly when visiting.